(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the study of tourism discourse, it is important to determine its typological status. There are different points of view on this matter. In particular, it is suggested that this type of speech is a subtype of institutional advertising speech. According to another point of view, it is an independent type of speech that has the ability to interact with other types of speech (domestic, scientific, advertising, etc.).